KETAHANAN PANGAN RUMAH TANGGA PETANI PENGHASIL BERAS ORGANIK - Anang Suhardianto; Yayuk Farida Baliwati; Dadang Sukandar (Jurnal Gizi dan Pangan, 2007)
The study was designed to analyze level of household food security of farmers who plant organic rice and identify landholding that supporting household food security. For that purposes, 61 samples of household were selected from farming households in Ciburuy Village, Bogor Regency. Data collected was landholding, working capital, cooperation, education, purposes of practicing on organic farming, waste management, knowledge of organic farming, organic rice productivity, income, food consumption and level of household food security. Food recall 1 X 24 hours and food frequency (weekly, monthly, and yearly) were used to obtain food consumption data. Household food security was determined based on level of energy consumption. Landholding that supporting household food security was determined based on rice consumption and household productivity. The analyses results of household food security showed that 85.2% of households were secure and 14.8% were insecure. Variables that significantly influenced household food security were income, knowledge of organic farming, organic rice productivity, purposes of practicing on organic farming, landholding, and waste management. Pearson correlation analyses showed that income, knowledge of organic farming, organic rice productivity, and landholding had significant effect toward  household food security. Spearman correlation analyses showed that purposes of practicing on organic farming and waste management had significant association with household food security too.  Based on daily average of energy sufficiency, land-man ratio should be 318 m2/person.